Analysis of lightweight composite sections with reinforced concrete infill with autoclaved aerated concrete (AAC) - Okasha, Mostafa Ali Taha Ali; Abdel Razek, Mohamed; El-Esnawi, Hassan; Alkhatib, Soliman (Frontiers in Built Environment, 2023)
The development of the composite section is of great importance in structural design, while the aim is to reduce weight and deflection in a way that does not affect the composite section's strength and durability. This paper studies the computational analysis of the composite section where the reinforced concrete was replaced with Autoclaved Aerated Concrete (AAC) in the compression zone. The theory of the first principles of concrete, together with Hook's law, were adopted to find flexure, shear, equivalent modulus of elasticity, effective moment of inertia, and deflection. Results were discussed and investigated using the finite element models developed by the ANSYS WORKBENCH software program. We found that the proposed analytical model can effectively provide the solution for the composite cross-section.